Characterization of occupational exposure to pesticides and its impact on the health of rural women - Carolina Panis; Shaiane Carla Gaboardi; Aedra Carla Bufalo Kawassaki; Elaine Christine Minatti Dias; Gessica Tuani Teixeira; Danilo Rodrigues Pereira da Silva; Daniel Rech; Luciano Zanetti Pessôa Candiotto (São Paulo State University (UNESP), 2022)
Objective: To characterize the profile of occupational exposure to pesticides and its impact on women's health. Method: This is a prospective and descriptive study with a quantitative approach. The study population included all patients attended at Francisco Beltrao Cancer Hospital (Ceonc) from May 2015 to December 2018 (n=315). The characterization of their exposure profile was obtained through an interview using a form applied by trained researchers contained 60 questions related to women's pesticide exposure and their health status. The questions referred to past and current occupational pesticide exposure profile, intoxication, and health history from women and their families. All collected data were analyzed in the Statistical Package for the Social Sciences package (SPSS 25.0). Results: A total of 265 individuals (84.2%) have lived some part of their life in the countryside, and 70% were categorized as occupationally exposed to pesticides. Most of them (57%) were directly exposed, mainly by washing pesticide-contaminated clothes and personal protective equipment used in pesticide pulverization without glove protection. Cancer cases in the family were the main disease reported (68.3%). Further, 57% of interviewed women had a breast cancer diagnosis but no significance between breast cancer occurrence and pesticide exposure was observed. Conclusion: The form allowed us to characterize the profile of occupational pesticide exposition in rural women, alerting them to their severe contamination. This approach can be useful to characterize the occupational exposure profiles of rural workers living in other rural regions of Brazil that use pesticides.